2006
DOI: 10.1302/0301-620x.88b6.16995
|View full text |Cite
|
Sign up to set email alerts
|

The effects of operative delay on the relief of neuropathic pain after injury to the brachial plexus

Abstract: We investigated the effect of delay before nerve repair on neuropathic pain after injury to the brachial plexus. We studied 148 patients, 85 prospectively and 63 retrospectively. The mean number of avulsed spinal nerves was 3.2 (1 to 5). Pain was measured by a linear visual analogue scale and by the peripheral nerve injury scale. Early repair was more effective than delayed repair in the relief from pain and there was a strong correlation between functional recovery and relief from pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 10 publications
2
51
2
3
Order By: Relevance
“…In a study of patients with a brachial plexus avulsion injury, Htut et al found the greatest pain to be in patients who had not had reconstructive surgery 5 . Kato et al reported positive correlations between pain intensity and the number of nerve root avulsions and a longer interval between the injury and surgery 59 . In the present study, we did not examine root avulsions specifically, but we did find that patients with a brachial plexus injury had more pain and disability than did those with a distal nerve injury and that pain intensity was a significant predictor of disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of patients with a brachial plexus avulsion injury, Htut et al found the greatest pain to be in patients who had not had reconstructive surgery 5 . Kato et al reported positive correlations between pain intensity and the number of nerve root avulsions and a longer interval between the injury and surgery 59 . In the present study, we did not examine root avulsions specifically, but we did find that patients with a brachial plexus injury had more pain and disability than did those with a distal nerve injury and that pain intensity was a significant predictor of disability.…”
Section: Discussionmentioning
confidence: 99%
“…Pain following traumatic nerve injuries has been reported to be associated with poor outcomes 5,15,[59][60][61] . Brachial plexus injury is often associated with more severe pain and is a significant predictor of disability.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have reported pain predominantly included patients following brachial plexus nerve injuries. 15,26,27,[48][49][50][51][52][53][54] In these studies, traumatic injuries, root avulsions, and injuries proximal to the dorsal root ganglion were associated with more pain; surgical intervention and the timing of surgery relative to injury were identified as important factors in alleviating pain. These outcome studies reported pain intensity and frequency but did not include validated patient-report questionnaires to assess the impact of the pain or impairment on the patient.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In the surgeons' general comments submitted in the survey, "chronic neuropathic pain" was often attributed to neuropathic pain, which was uncontrolled and nonresponsive to treatment. Neuropathic pain and cold sensitivity are frequently reported as contributing to poor outcome following nerve injury [6,12,19,20,25,[27][28][29]32]. However, few outcome studies provide details regarding these patient symptoms, and most studies of nerve injured patients report only motor and sensory function.…”
Section: Discussionmentioning
confidence: 99%
“…Many outcome studies of nerve-injured patients present motor and sensory functional outcomes but do not report information regarding the absence or presence of pain [1,7,16,17,30,35,36,38,41,44]. In the surgical literature, many studies that report pain in nerve-injured patients generally use unidimensional measures (verbal ratings or visual analog scales of pain intensity) and do not include assessment of the psychosocial factors that may be associated with pain [5,8,28,32,34,40,42].…”
Section: Introductionmentioning
confidence: 99%